Intrathecal analgesia in patients with cancer pain--an audit in a tertiary institution - Pasutharnchat, Koravee; Tan, Kian-Hian; Mohamed, Rozilah @ Abdul Hadi; Ho, Kok-Yuen (Academy of Medicine, Singapore, 2009)
Cancer pain is one of the most frequently encountered pain syndromes. With the application of the World Health Organization analgesic ladder, adequate analgesia is achieved in 75% to 90% of patients. The remaining patients suffer from intractable pain requiring intrathecal analgesia. The aim of this study was to retrospectively analyse the pain intensity before and after intrathecal analgesia and review the complications associated with the implantation and the care of the intrathecal device. Materials and Methods: We reviewed medical records of all cancer patients whose pain were managed by intrathecal catheter implants in our centre from February 2005 to August 2008. The pain intensity, medication and complications related to intrathecal catheter insertion or drug delivery were reviewed at the time before starting the intrathecal analgesia (T0) and time of discharge from the hospital/time prior to death during their stay in the hospital (Tdsc). Results: Twenty-nine patients were included. Out of these 29 patients, 86.2% had metastatic cancer. The most common indication was poor pain control. Pain intensity was reduced signifi cantly at the time of discharge from hospital (P <0.001). The number of patients with side effects from opioids decreased after intrathecal treatment. We found 4 patients with short-term catheter complications e.g. kinked or displaced catheter and catheter-related infection. Conclusion: Intractable cancer pain could be managed effectively by intrathecal analgesia with a signifi cant decrease in pain intensity and reduced opioid-related side effects. The side effects due to intrathecal opioids and complications from intrathecal catheter were minimal.